Improving international students’ acculturation and Chinese vocabulary through problem-based learning with augmented reality - Yirong Jiang; Thoriq Tri Prabowo; Thanin Ratana-Olarn (International Journal of Evaluation and Research in Education (IJERE), 2026)
The integration of problem-based learning (PBL) and augmented reality (AR) has emerged as a promising approach to improve language learning and acculturation. This study aimed to develop and evaluate a problem-based learning and augmented reality (PBLAR) instructional model to enhance international students’ acculturation and Chinese vocabulary. The study used a quasi-experimental design with 70 first-year international students randomly assigned to an experimental group (EG) (PBLAR, n=35) or a control group (CG) (traditional teaching method, n=35). The intervention lasted two weeks, and both groups completed a pre-test to ensure baseline comparability. The EG achieved significantly higher post-test scores in Chinese vocabulary (F=296.65, p<0.001) and acculturation (F=840.62, p<0.001). In this context, PBLAR demonstrated stronger short-term outcomes in Chinese vocabulary and acculturation; it should be viewed as a complementary pedagogy that highlights the value of integrating PBL and AR. Findings highlight PBLAR’s potential for immersive, problem-driven language instruction that bridges technology and pedagogy in multicultural contexts.